2021
DOI: 10.1186/s12935-021-02340-w
|View full text |Cite
|
Sign up to set email alerts
|

TMED3/RPS15A Axis promotes the development and progression of osteosarcoma

Abstract: Background Osteosarcoma is a primary malignant tumor that mainly affects children and young adults. Transmembrane emp24 trafficking protein 3 (TMED3) may be involved in the regulation of malignant cancer behaviors. However, the role of TMED3 in osteosarcoma remains mysterious. In this study, the potential biological function and underlying mechanism of TMED3 in progression of osteosarcoma was elaborated. Methods The expression of TMED3 in osteosarc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 72 publications
0
9
0
Order By: Relevance
“…53 In-vitro studies have shown that the downregulation of RPS15A suppresses the cellular proliferation of osteosarcoma, lung cancer, breast cancer, acute myeloid leukemia and hepatocellular carcinoma. 54 Overexpression of RPS15A promotes proliferation, metastasis and EMT via activation of the AKT signaling pathway in gastric cancer cells. 55 Despite the important component of the ribosomal complex, the role of RPS15A in the NED of PCa is not fully understood.…”
Section: Conflict Of Interest Statementmentioning
confidence: 99%
“…53 In-vitro studies have shown that the downregulation of RPS15A suppresses the cellular proliferation of osteosarcoma, lung cancer, breast cancer, acute myeloid leukemia and hepatocellular carcinoma. 54 Overexpression of RPS15A promotes proliferation, metastasis and EMT via activation of the AKT signaling pathway in gastric cancer cells. 55 Despite the important component of the ribosomal complex, the role of RPS15A in the NED of PCa is not fully understood.…”
Section: Conflict Of Interest Statementmentioning
confidence: 99%
“…TMED3 plays a role in the selection and secretion of COP vesicles in the ER-GC network and modulates several signaling pathways. TMED3 expression is strongly upregulated in several cancer types (including osteosarcoma, breast cancer, chordoma, HCC and non-small cell lung cancer (NSCLC)) and correlates with poor prognosis in patients [54][55][56][57]121]. TMED3 function is required for WNT ligands normal intracellular localization, trafficking and secretion [122,123].…”
Section: Tmed Family Of P24 Proteinsmentioning
confidence: 99%
“…The oncogenic role of TMED3 was also verified in breast cancer development through clinicopathological data and in vitro and vivo experiments [ 10 ]. TMED3 knockdown also inhibited osteosarcoma cell proliferation and tumor growth by inhibiting RPS15A [ 11 ]. However, TMED3 was also reported as a metastatic suppressor and knocking down TMED3 could promote metastatic growth in human colon cancer [ 12 ].…”
Section: Introductionmentioning
confidence: 99%